Poverty Alleviation Strategy Policy Formulation in Toba Regency, North Sumatra Province - Marlan Hutahaean; Dimpos Manalu; Johnson Pasaribu (Indonesian Association for Public Administration (IAPA), 2020)
This paper aims to uncover the process of public policies formulation, specifically regarding poverty reduction strategies and social protection in Toba Regency, North Sumatra. The poverty reduction policy that is the focus of this research consists of three Regional Regulations (Perda), which were only issued in 2019, after the district was established (autonomy) since 1999, namely: Regional Regulation No. 2/2019 concerning the Implementation of Social Welfare, Regional Regulation No. 10/2019 concerning Protection and Fulfillment of the Rights of Persons with Disabilities, and Regional Regulation Number policy formulation11/2019 concerning the Implementation of Elderly Welfare. This qualitative research concludes that the process and formulation of poverty reduction policies in Toba Regency took place technocratically and elitist. First, the three Regional Regulations are considered as